Reliability of Acid-Insoluble Ashes and Undigestible Neutral Detergent Fibre as Internal Markers for Estimation of Digestibility in Beef Cattle Fed High-Concentrate Diets - Amira Arbaoui; Antonio de Vega (Agriculture, 2025)
Digestibility, together with intake, is the main factor affecting animal productivity. It can be assessed in vivo by measuring total feed intake and faecal output (time-consuming and labour-intensive) or with the aid of substances known as markers. Internal markers such as acid insoluble ash (AIA) or undigestible neutral detergent fibre (uNDF) have been alleged to be preferable for digestibility estimations. The use of AIA and uNDF for digestibility estimation in beef cattle fed high-concentrate and barley straw diets has been rarely documented; hence, the objectives of the present paper were to compare digestibility values obtained by total faecal collection vs. AIA or uNDF (Experiment 1), to compare digestibility values obtained using Cr2O3 as an external marker vs. AIA or uNDF (Experiment 2), and to compare digestibility values obtained using AIA vs. uNDF in beef cattle fed high-concentrate and barley straw diets (Experiment 3). Faecal recoveries of AIA and uNDF (Experiment 1) were very variable and likely influenced by contamination of faeces and/or feedstuffs with soil and/or dust. Then, the regressions between digestibility values obtained in metabolism cages or using Cr2O3 as an external marker and AIA or uNDF were not significant. The use of these two latter markers for estimation of digestibility in beef cattle fed high-concentrate and barley straw diets is not recommended.